Discovery learning in English Language Teaching - Ayende, Edewale; Bleza, Edenkelu (Educia Journal, 2023)
This article discuss about discovery learning model that suitable for learning to identify observation result report text, because in discovery learning model students practice for independent learning, develop students' creativity and knowledge in learning. Discovery Learning (discovery) is a teaching method that regulates teaching in such a way that children acquire knowledge they previously did not know, not through notification, partly or wholly discovered by themselves. In discovery learning (discovery) activities or learning designed in such a way that students can discover concepts and principles through their own mental processes. In finding concepts, students make observations, classify, make assumptions, explain, draw conclusions and so on to find some concepts or principles. This article aim to improve student English skill using discovery learning method.